Political culture and political consciousness - Natela Basilashvili (Genius Journals, 2021)
Structural and functional features of politics and political space are determined by value and normatively oriented dimensions. Political interests and goals are reflected in certain values and orientations that create a functional model of political life. Such a model of political life is called a political system, which is a space of its own institutional and value orientation. Structural and functional features of politics and political space are determined by value and normatively oriented dimensions
Keywords: Politics; state; power; society